Autonomy, Competence, Relatedness, and Beneficence: A Multicultural Comparison of the Four Pathways to Meaningful Work - Martela, Frank; Riekki, Tapani J. J. (Frontiers in Psychology, 2018)
Meaningful work is a key element of positive functioning of employees, but what makes work meaningful? Based on research on self-determination theory, basic psychological needs, and prosocial impact, we suggest that there are four psychological satisfactions that substantially influence work meaningfulness across cultures: autonomy (sense of volition), competence (sense of efficacy), relatedness (sense of caring relationships), and beneficence (sense of making a positive contribution). We test the relationships between these satisfactions and perceived meaningful work in Finland (n = 594, employees of several organizations), India (n = 342, collected through Mturk), and the USA (n = 373, collected through Mturk). Regression analyses show that – except for competence in USA – all four satisfactions are significantly and independently associated with meaningful work. Moreover, structural equation modeling shows that they fully mediated the relationship between occupational position and work meaningfulness in India and in the USA. In sum, the results support the importance of these four satisfactions in explaining the psychological underpinnings of meaningful work.